Survival of surf scoters and white‐winged scoters during remigial molt. Issue 7 (27th August 2014) - Uher‐Koch, Brian D.; Esler, Daniel; Dickson, Rian D.; Hupp, Jerry W.; Evenson, Joseph R.; Anderson, Eric M.; Barrett, Jennifer; Schmutz, Joel A.
ABSTRACT Quantifying sources and timing of variation in demographic rates is necessary to determine where and when constraints may exist within the annual cycle of organisms. Surf scoters (Melanitta perspicillata) and white‐winged scoters (M. fusca) undergo simultaneous remigial molt during which they are flightless for >1 month. Molt could result in reduced survival due to increased predation risk or increased energetic demands associated with regrowing flight feathers. Waterfowl survival during remigial molt varies across species, and has rarely been assessed for sea ducks. To quantify survival during remigial molt, we deployed very high frequency (VHF) transmitters on surf scoters (n = 108) and white‐winged scoters (n = 57) in southeast Alaska and the Salish Sea (British Columbia and Washington) in 2008 and 2009. After censoring mortalities potentially related to capture and handling effects, we detected no mortalities during remigial molt; thus, estimates of daily and period survival for both scoter species during molt were 1.00. We performed sensitivity analyses in which mortalities were added to the dataset to simulate potential mortality rates for the population and then estimated the probability of obtaining a dataset with 0 mortalities. We found that only at high survival rates was there a high probability of observing 0 mortalities. We conclude that remigial molt is normally a period of low mortality in the annual cycle of scoters. The molt period does not appear to be a constraint on scoter populations; therefore, other annual cycle stages should be targeted by research and management efforts to change population trajectories. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.